Creating job opportunities through humanizing entrepreneurship education in Somalia - Omar, Mohamed Warsame; Ahmad Dahlan, Abdul Rahman; Ahmad H.Osman, Rahmah (Research Publish Journals, 2019)
Educating youth to become entrepreneurs is a vital factor in creating employment and eradicating poverty. The primary concern of relevant and innovative entrepreneurial-ism is that it creates wealth for the entrepreneurs; creates job opportunities for the general population and also creates and sustains local economy growth. This paper examines the role of humanizing entrepreneurship education and how it could help in job creation in Somalia. Also this paper discusses on how educating youth to become entrepreneurs can contribute to enhancing the youth satisfaction and loyalty to their country, happiness and their well-being. Finally this paper provides the business models, strategies and plans to implement humanizing Entrepreneurship education in Somalia in order to nurture youths with the knowledge, skill and virtues. These youths can start their own businesses and create employment for others.